Overexpression of TIMP3 Protects Against Cardiac Ischemia/Reperfusion Injury by Inhibiting Myocardial Apoptosis Through ROS/Mapks Pathway - Hui Liu; Xibo Jing; Aiqiao Dong; Baobao Bai; Haiyan Wang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Myocardial ischemia/reperfusion (I/R) injury remains a great challenge in clinical therapy. Tissue inhibitor of metalloproteinases 3 (TIMP3) plays a crucial role in heart physiological and pathophysiological processes. However, the effects of TIMP3 on I/R injury remain unknown. Methods: C57BL/6 mice were infected with TIMP3 adenovirus by local delivery in myocardium followed by I/R operation or doxorubicin treatment. Neonatal rat cardiomyocytes were pretreated with TIMP3 adenovirus prior to anoxia/reoxygenation (A/R) treatment in vitro. Histology, echocardiography, in vivo phenotypical analysis, flow cytometry and western blotting were used to investigate the altered cardiac function and underlying mechanisms. Results: The results showed that upregulation of TIMP3 in myocardium markedly inhibited myocardial infarct areas and the cardiac dysfunction induced by I/R or by doxorubicin treatment. TUNEL staining revealed that TIMP3 overexpression attenuated I/R-induced myocardial apoptosis, accompanied by decreased Bax/Bcl-2 ratio, Cleaved Caspase-3 and Cleaved Caspase-9 expression. In vitro, A/R-induced cardiomyocyte apoptosis was abrogated by pharmacological inhibition of reactive oxygen species (ROS) production or MAPKs signaling. Attenuation of ROS production reversed A/R-induced MAPKs activation, whereas MAPKs inhibitors showed on effect on ROS production. Furthermore, in vivo or in vitro overexpression of TIMP3 significantly inhibited I/R- or A/R-induced ROS production and MAPKs activation. Conclusion: Our findings demonstrate that TIMP3 upregulation protects against cardiac I/R injury through inhibiting myocardial apoptosis. The mechanism may be related to inhibition of ROS-initiated MAPKs pathway. This study suggests that TIMP3 may be a potential therapeutic target for the treatment of I/R injury.